Regulation and structure of an Escherichia coli gene coding for an outer membrane protein involved in export of K88ab fimbrial subunits. - Mooi, F R (1986)
The nucleotide sequence of the faeD gene of Escherichia coli and the amino acid sequence of its product is presented. The faeD product is an outer membrane protein required for transport of K88ab fimbrial subunits across the outer membrane. The protein is synthesized as a precursor containing a signal peptide, and the tentative mature protein comprises 777 amino acid residues. The distribution of amino acids in the faeD protein is similar to that of other outer membrane proteins; showing a fairly even distribution of charged residues and the absence of extensive hydrophobic stretches. Secondary structure predictions revealed a region of 250 amino acid residues which might be embedded in the outer membrane. The 5'-end of faeD is located within a region showing dyad symmetry. This region serves to couple translation of faeD to the translation of the gene preceding it (faeC). The 3'-end of faeD shows an overlap of 5 bases with the next gene (faeE).